2023
DOI: 10.3390/life13051176
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Cancer Effect of Cinnamon Aqueous Extract: A Focus on Hematological Malignancies

Abstract: Cinnamon is an evergreen and tropical plant of the family Lauraceae, growing particularly in Sri Lanka, whose aqueous extract has been tested in different studies to evaluate its possible use as an anti-cancer compound. Both in vitro and in vivo experiments seem to confirm that it acts on various cellular pathways, contributing to down-regulating the activity of molecules that stimulate the proliferation and survival of cells such as the transcription factors NF-KB and AP-1, COX-2, dihydrofolate reductase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 110 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…C. verum commonly known as Cinnamon, exhibits anti-cancer, antioxidant, anti-lipid, and anti-fibrotic properties 17 , 54 It demonstrates anticancer effects against various cancer cell types, including breast cancer, through apoptosis induction and angiogenesis suppression. This extends to its efficacy against lung and colon cancer cells 55 , 56 . C. longa , or Turmeric, is recognized for its potent anti-cancer properties, effectively inhibiting the growth of various cancer cells such as those in breast, prostate, and colon cancers 57 59 .…”
Section: Resultsmentioning
confidence: 84%
“…C. verum commonly known as Cinnamon, exhibits anti-cancer, antioxidant, anti-lipid, and anti-fibrotic properties 17 , 54 It demonstrates anticancer effects against various cancer cell types, including breast cancer, through apoptosis induction and angiogenesis suppression. This extends to its efficacy against lung and colon cancer cells 55 , 56 . C. longa , or Turmeric, is recognized for its potent anti-cancer properties, effectively inhibiting the growth of various cancer cells such as those in breast, prostate, and colon cancers 57 59 .…”
Section: Resultsmentioning
confidence: 84%
“…Regarding the clinical features, earlier research has revealed that most patients at risk are female, have an average age of 65.3 years, and that the mandible is the most often affected jawbone [3,4]. ONJ consists of three stages: (i) Stage 0 does not involve a fistula or exposed bone, it is considered a possible precursor to the disease; odontalgia, maxillary sinus discomfort, jaw pain that may extend to the temporomandibular joint region, and altered feeling in the maxilla and mandibular areas are among the symptoms; there could be movement of a tooth and intraoral or extraoral edema that isn't connected to periodontal disease, such as the absence of formation of new bone in the extraction socket, alterations of the structure of bone, osteosclerosis regions, and thickening of the periodontal ligament [5]; (ii) Stage 1 involves a fistula or exposed necrotic bone without any signs of inflammation; radiographic images may be limited to the alveolar bone region and resemble those of Stage 0; (iii) in Stage 2, patients exhibit symptoms such as an exposed necrotic bone or a fistula, along with signs of infection and inflammation; (iv) Stage 3 is characterized by an exposed and necrotic bone or fistulae that probes the bone, along with infection and pathological fracture, extraoral fistula, oral-antral or oral-nasal communication, osteolysis extending to the inferior border of the mandible or sinus floor, or exposed necrotic bone extending beyond the region of the alveolar bone as complications [6][7][8].…”
Section: Osteonecrosis Of the Jawmentioning
confidence: 99%
“…In fact, it alters the mitochondrial membrane potential, causing downregulation of the NAD-dependent histone deacetylase Sirtuin-1 (HDAC SIRT-1) and leading to an increase in superoxide synthesis. As it is noted, miR-122 is downregulated and acts as a tumor suppressor in different types of cancer, like breast cancer, through an inhibition of cell migration, proliferation, and invasion; it would be very interesting to target miRNAs expression using natural substances in combination with traditional drugs in the treatment of cancer in order to potentiate the efficacy of conventional molecules and reduce the adverse effects [46,53,54]. Branched-chain amino acids (BCAAs), including leucine, isoleucine, and valine, are molecules with an aliphatic sidechain with a branch that cannot be produced by human organisms and must be introduced with food or be synthetized from gut microbes, specifically from Prevotella copri and Bacteroides vulgatus.…”
Section: Modulation Of Redox Signalling and Regulation Of Foxp3+ T Cellsmentioning
confidence: 99%